Quantitative Job Insecurity and Well-Being: Testing the Mediating Role of Hindrance and Challenge Appraisals - Charkhabi, Morteza (Frontiers in Psychology, 2019)
The aim of this study is to determine the extent to which cognitive appraisals of job insecurity may mediate the link between job insecurity and well-being among employees. According to cognitive appraisal theory, the two cognitive appraisals of job insecurity, hindrance vs. challenge appraisals, were integrated into a conceptual model and examined as the mediators of job insecurity-wellbeing association. Well-being related outcomes were job satisfaction and emotional exhaustion. Hypotheses were tested using a total sample of 306 hospital staff. Respondents from diverse departments of this hospital were recruited and completed scales on quantitative job insecurity, hindrance vs. challenge appraisals of job insecurity, job satisfaction, and emotional exhaustion. Results indicated that hindrance appraisals of job insecurity mediated the association between job insecurity and emotional exhaustion. Challenge appraisals did not mediate the job insecurity-well-being association. In all, only one out of four mediation paths was found significant. As a result, employees hindered by job insecurity are more likely to be emotionally exhausted by perceived job insecurity.